Utilising Appreciative Inquiry (AI) in Creating a Shared Meaning of Ethics in Organisations - Vuuren, L. J. van (Journal of business ethics, 2005)
The management of ethics within organisations typically occurs within a problem-solving frame of reference. This often results in a reactive, problem-based and externally induced approach to managing ethics. Although basing ethics management interventions on dealing with and preventing current and possible future unethical behaviour are often effective in that it ensures compliance with rules and regulations, the approach is not necessarily conducive to the creation of sustained ethical cultures. Nor does the approach afford (mainly internal) stakeholders the opportunity to be co-designers of the organisation’s ethical future. The aim of this paper is to present Appreciative Inquiry (AI) as an alternative approach for developing a shared meaning of ethics within an organisation with a view to embrace and entrench ethics, thereby creating a foundation for the development of an ethical cul- ture over time. A descriptive case study based on an application of AI is used to illustrate the utility of AI as a way of thinking and doing to precede and complement problem-based ethics management systems and interventions.